Educação em Angola: Experiência, Pesquisa e Esperança - Nambua, Manuel (2024)
Each viewpoint of a study can indeed be the standpoint of a point. In this perspective, the present study emerges, inquisitive and qualitative in nature, conducting a thorough critical analysis of education and teacher training in Angola based on bibliographic research from theses and dissertations carried out by Angolan researchers in Brazilian universities, within postgraduate programs in Education. To achieve this, we aim to address the following research questions: What do studies produced in Brazil say about education in Angola? What are the main limitations and challenges in teacher training in Angola? Despite Angola being a country rich in mineral resources, why are education and teacher training still inadequate? What narratives are told in studies about the highlighted territory? To answer these questions, we mapped research in the Capes Theses and Dissertations Catalog database, refining 34 works after measurement, excluding 24, and analyzing 11 research studies. The results of the studies indicate that teacher training in Angola is still deficient, despite various educational reforms implemented by the government. Furthermore, training lacks greater attention regarding funding and educational policies. Given the evident scarcity of studies dedicated to pre-colonial education in Angola and scientific investigation, it is important to highlight the disagreement concerning the chronology of events related to the Portuguese invasion in Angola, particularly regarding the numerical data from the years 1482 and 1483. Therefore, aiming to reverse this situation, at the end of the studies, we propose an inventory based on keywords, focusing on the five vowels (A, E, I, O, U), to foster hope in education in Angola. This study is expected to emerge as a relevant and academic contribution to the body of knowledge about Angolan education. The plurality of perspectives offered by this research can enrich academic debates and foster deep reflections in the social, and perhaps, political sphere.